KOMPETENSI GURU REGULER DI SEKOLAH INKLUSIF DALAM PEMBELAJARAN BAGI SISWA TUNARUNGU - Murni Winarsih (Perspektif Ilmu Pendidikan, 2013)
The aim of this study is to explore the teachers’s competency in teaching students with hearing impairments within inclusive educational settings. This research conducted from February 2012 through June 2013. Method of the research is qualitative descriptive, observation and interview were employed to gather the necessary data towards 5 teachers where there is at least one student with hearing impairment in their classroom across all educational level. The result shows that the teachers do not have the competency about teaching the hearing impairments. The teachers have never been trained on teaching and instruction of children with hearing impairment, because the training based on contextual learning has not been previous. The research results some implication and recomendation.